The big-eyed bug genus Germalus Stål, 1862 in New Guinea (Heteroptera: Lygaeoidea: Geocoridae) - Kóbor, Péter; Kondorosy, Előd (Zootaxa, 2022)
An overview of the representatives of the geocorine true bug genus, Germalus Stål, 1862, distributed in New Guinea is presented. The results include the description of Germalus cucullatus sp. nov., Germalus kontschani sp. nov., Germalus pappi sp. nov., Germalus pulchellus sp. nov. and Germalus sellatus sp. n. and the discussion of their relationship to other Germalus species in the adjacent regions. Key to New Guinean species and distribution maps are provided.